2001
DOI: 10.1183/09031936.01.17508560
|View full text |Cite
|
Sign up to set email alerts
|

High or standard initial dose of budesonide to control mild-to-moderate asthma?

Abstract: High or standard initial dose of budesonide to control mild-to-moderate asthma? P. Chanez, R. Karlstrom, P. Godard. #ERS Journals Ltd 2001. ABSTRACT: Guidelines on the use of inhaled steroids in asthma advocate that the daily dose should be chosen according to the severity of the disease. However, the question of the optimal starting dose remains to be properly addressed, as does the issue of the adjustment in dose required for a given patient.Whether a high initial dose of budesonide (800 mg b.i.d) was more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 21 publications
3
14
0
2
Order By: Relevance
“…The findings are also consistent with other dose-response studies of budesonide that did not include a placebo arm and as a result could not be included in this meta-analysis [21][22][23][24][25][26][27][28]. For example, similar results were found in the studies by CHANEZ et al [22] and TUKIAINEN et al [23], which showed no difference between initial treatment with 400 or 1,600 mg?day -1 budesonide after 4 weeks, or with 200 or 800 mg?day -1 after 12 weeks, respectively.…”
Section: Key Findingssupporting
confidence: 85%
See 2 more Smart Citations
“…The findings are also consistent with other dose-response studies of budesonide that did not include a placebo arm and as a result could not be included in this meta-analysis [21][22][23][24][25][26][27][28]. For example, similar results were found in the studies by CHANEZ et al [22] and TUKIAINEN et al [23], which showed no difference between initial treatment with 400 or 1,600 mg?day -1 budesonide after 4 weeks, or with 200 or 800 mg?day -1 after 12 weeks, respectively.…”
Section: Key Findingssupporting
confidence: 85%
“…For example, similar results were found in the studies by CHANEZ et al [22] and TUKIAINEN et al [23], which showed no difference between initial treatment with 400 or 1,600 mg?day -1 budesonide after 4 weeks, or with 200 or 800 mg?day -1 after 12 weeks, respectively. In the FACET study [25], there were clinically significant improvements in asthma control with budesonide taken over a 12-month period at 800 as compared to 200 mg?day -1 .…”
Section: Key Findingssupporting
confidence: 84%
See 1 more Smart Citation
“…A dose of beclomethasone (200 mg twice daily) that is within the recommended starting-dose range (200-500 mg) of the Global Initiative for Asthma guidelines was chosen [11]. In addition, CHANEZ et al [23] showed that both high (800 mg) and standard (200 mg) initial doses of budesonide were equally effective in controlling symptoms and improving lung function in mildto-moderate asthma. The dose of montelukast is the labelled dose for adults (10 mg once daily), as established in dose-ranging studies [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…ICS and ICS/ LABA are used as a first choice for asthma treatment around the world. The effectiveness of ICS and ICS/LABA for asthma treatment is supported in plural large clinical trials [21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%